Mandatory Audit Firm Rotation and Audit Quality - Sissons, Amanda; Trombetta, Marco (Taylor & Francis, 2014)
In a setting where mandatory audit firm rotation has been effective for more than 20 years (i.e., Italy), we analyse changes in audit quality during the auditor engagement period. In our research setting, auditors are appointed for a three-year period and their term can be renewed twice up to a maximum of nine years. Since the auditor has incentives to be reappointed at the end of the first and the second three-year periods, we expect audit quality to be lower in the first two three-year periods compared to the third (i.e. the last) term. Assuming that a better audit quality is associated with a higher level of accounting conservatism, and using abnormal working capital accruals (AWCA) as a proxy for the latter, we find that the auditor becomes more conservative in the last three-year period, i.e. the one preceding the mandatory rotation. These results are confirmed using Basu’s (1997) timely loss recognition model. In an additional analysis, we use earnings response coefficients as a proxy for investor perception of audit quality, and we observe results consistent with an increase in audit quality perception in the last engagement period.
Keywords: mandatory rotation;audit firm rotation;audit quality;auditor tenure;auditor conservatism; mandatory rotation; audit firm rotation; audit quality; auditor tenure; auditor conservatism; 53 Ciencias Económicas; ODS 16 - Paz, justicia e instituciones sólidas